Karakteristik Fisik, Kimiawi dan Sensoris Nuget Bandeng Tinggi Protein dan Zat Besi dengan Penambahan Tepung Kelor untuk Intervensi Gizi Pencegahan Stunting: Karakteristik Fisik, Kimiawi, dan Sensoris Nuget Bandeng Tinggi Protein dan Zat Besi dengan Penambahan Tepung Kelor untuk Intervensi Gizi Pencegahan Stunting - Melvina Aristiani; Hiasinta Anatasia Purnawijayanti; Fransisca Shinta Maharini (Amerta Nutrition, 2022)
Background: Stunting can be prevented with specific nutritional interventions for young women as future mothers. Iron deficiency anemia in expectant mothers is a risk factor for stunting, and its incidence in adolescents in Indonesia is still high. It is necessary to develop products that are sources of protein and iron that teenagers like, such as nuggets. Milkfish and moringa are rich in protein and iron which have the potential to be processed into nuggets as a source of protein and iron so that they can be used in nutritional interventions in adolescents to prevent stunting. Objectives: Knowing the physical, chemical, and sensory characteristics of milkfish nuggets with the addition of moringa flour. Methods: An experimental study with a completely randomized design with 5 levels of moringa flour content (0-10%) and 3 treatment repetitions. The data included water holding capacity and cooking losses, protein and iron content, and sensory properties of the nuggets (appearance, texture, taste, aftertaste, and overall acceptability). Physical and chemical test data were analyzed by Variant Analysis or Kruskal Wallis according to the data category, sensory test data were analyzed by Friedman test Results: The addition of moringa flour did not affect the protein and iron content of the nuggets. Nuget protein content ranges from 12.78–13.62%, and iron content between 3.81-5.41% mg. The addition of moringa flour affected the nuggets' cooking shrinkage and water-holding capacity. The higher the content of Moringa flour, it tends to reduce the water holding capacity and increase the cooking shrinkage of the nuggets. The addition of moringa flour affected all the sensory properties of the nugget. The higher the moringa flour content tends to lower the nugget sensory score. Conclusions: High protein and a source of iron nuggets for stunting prevention interventions can be developed from milkfish with the addition of moringa flour.